SISTEM INFORMASI PADA KLINIK KECANTIKAN DR. INOY JAMBI BERBASIS WEB: MYSQL, PHP, INFORMATION SYSTEMS, DR.INOY'S BEAUTY CLINIC, WEB. - Suana, Irma (LP2M STMIK Nurdin Hamzah Jambi, 2019)
In the era of globalization, as currently the development of technology has experienced significant progress. Improved information systems are expected to be able to help a company to be more competitive and can further improve the effectiveness of a company. One information system that can be improved in a company is in terms of marketing transactions, sales, purchases and management of inventory data. Dr. Beauty Clinic Inoy Jambi has the intent and purpose of building a sales system with easy and fast access. But at the Beauty Clinic Dr. Inoy has not implemented an appropriate computerized system so employees often experience recording errors and loss of important data. Therefore, the writing of this thesis explains the stages regarding designing an Information System at Dr. Beauty Clinic. Inoy Jambi to facilitate the parties concerned to be able to find out product data, goods, customers, join members, employees, and sales transactions in order to produce product data reports and goods data reports, member data reports, employee data reports and sales transaction data reports . Making this system uses Web programming with PHP scripting languages ??and storage methods using MySQL databases related to research obtained through field studies and literature studies. The results of this study are expected to help facilitate the Beauty Clinic of Dr. Inoy stores important data related to member registration.